The LEGAL REVIEW OF RETROACTIVE PRINCIPLE IN CRIMES AGAINST HUMANITY - Intan Audy (Fakultas Hukum Universitas Kristen Indonesia, 2021)
The principle of retroactivity as the spirit of the law creates formal juridical problems. Constitutionally and in criminal law, there are regulations that prohibit retroactive enforcement of statutory regulations. This was motivated by the idea of ​​protecting human rights, but in the reform era the problem of retroactivity also emerged when discussing the issue of human rights crimes in the context of protecting human rights. Protection of citizens' human rights is the first parameter that determines the indicators of a country's democracy. Cases of crimes against humanity are still a wound for the community, so that it is the reality of human rights that is the most worrying to date. This is because the perpetrators of crimes against humanity were allegedly committed by state actors themselves, namely law enforcement officials, resulting in impunity. The principle of retroactivity in crimes against humanity can be based on lex superior derogat legi inferiori and lex specialist derogat legi generale, and are closely related to legal objectives. Legal principles are legal foundations, so they are expected to reveal the truth of the past so that national reconciliation can be realized.